Disentangling the family Blepharocorythidae (Ciliophora, Entodiniomorphida): a molecular assessment of morphological classification. Issue 5 (4th July 2021) - Cedrola, Franciane; Senra, Marcus Vinicius Xavier; Faulhaber, Francisco Romero; D'Agosto, Marta; Dias, Roberto Júnio Pedroso
Abstract : The family Blepharocorythidae comprehends 26 species of ciliates that colonize the hindgut of many fermenting mammals, where they play a critical role in the process of food digestion. Recent molecular phylogenetic works indicate this family might be polyphyletic, possibly a consequence of the historical use of weak diagnostic character (long vestibulum, single contractile vacuole, and anterior and posterior ciliary zones) that do not reflect evolutionary divergences. Here, we revisited and reinterpreted data from old taxonomic studies aiming to resolve taxonomical inconsistencies and to shed some light into the systematics of this family of ciliates. Accordingly, we have identified clear morphological and morphogenetic features to propose a new organization scheme, which is in consonance with molecular phylogenetic data, highlighting the importance of revisiting old literature to improve the systematics within Ciliophora or in any other group of organisms.